Adult neurogenesis in the four-striped mouse (Rhabdomys pumilio) and common mole rat (Cryptomys hottentotus) - Olaleye, Olatunbosun Oriyomi (My University, 2011)
Adult neurogenesis was investigated in captive bred four-striped mouse (Rhabdomys pumilio) and wild caught common mole-rat (Cryptomys hottentotus). Eight individuals per species were used in the study. The animals were anaesthetized and transcardially perfused with saline followed by 4% paraformaldehyde in 0.1 M phosphate buffer (PB), pH 7.4. Brains were removed and post fixed in the same fixative overnight. Following equilibration in 30% sucrose in PB, 50 μm frozen sections were cut in the saggital planes followed by BrdU immunohistochemistry. Ki-67 and doublecortin (DCX) staining was undertaken as an additional confirmatory staining for cell proliferation. BrdU, Ki-67 and DCX immunostainings confirmed adult neurogenesis in the subventricular zone (SVZ) of the lateral ventricle and dentate gyrus (DG) of the hippocampus of the four-striped mouse and common mole rat. The existence of adult neurogenesis was observed in potential sites namely, the striatum in the four-striped mouse and substantia nigra in both species. Immature neurons were observed in the cerebral cortex only in the common mole rat.